Predictors of premature discontinuation of outpatient treatment after discharge of patients with posttraumatic stress disorder - Wang HR (Dove Medical Press, 2015)
Hee Ryung Wang, Young Sup Woo, Tae-Youn Jun, Won-Myong Bahk Department of Psychiatry, College of Medicine, The Catholic University of Korea, Seoul, Korea Objective: This study aimed to examine the sociodemographic and disease-related variables associated with the premature discontinuation of psychiatric outpatient treatment after discharge among patients with noncombat-related posttraumatic stress disorder. Methods: We retrospectively reviewed the medical records of patients who were discharged with a diagnosis of posttraumatic stress disorder. Results: Fifty-five percent of subjects (57/104) prematurely discontinued outpatient treatment within 6 months of discharge. Comparing sociodemographic variables between the 6-month non-follow-up group and 6-month follow-up group, there were no variables that differed between the two groups. However, comparing disease-related variables, the 6-month follow-up group showed a longer hospitalization duration and higher Global Assessment of Function score at discharge. The logistic regression analysis showed that a shorter duration of hospitalization predicted premature discontinuation of outpatient treatment within 6 months of discharge. Conclusion: The duration of psychiatric hospitalization for posttraumatic stress disorder appeared to influence the premature discontinuation of outpatient treatment after discharge. Keywords: posttraumatic stress disorder, discontinuation, compliance, predictor